Helicobacter pylori, stomach cancer and its prevention in New Zealand. Issue 3 (2nd July 2020) - Signal, Virginia; Gurney, Jason; Inns, Stephen; McLeod, Melissa; Sika-Paotonu, Dianne; Sowerbutts, Sam; Teng, Andrea; Sarfati, Diana
ABSTRACT: Infection with Helicobacter pylori is the strongest modifiable risk factor for stomach cancer. Nine out of 10 people who develop stomach cancer in the distal part of the stomach have been infected with H. pylori . Infection of the gastric mucosa with H. pylori most commonly occurs during childhood and if not treated can cause chronic inflammation and gastric carcinogenesis. Stomach cancer is a major contributor to the ethnic gap in cancer incidence and mortality in New Zealand, with Māori and Pacific peoples having three to six times higher rates of stomach cancer than New Zealand Europeans. Infection with H. pylori is the main driver of this inequity. Testing asymptomatic individuals with non-invasive tests (serology, stool or C-urea breath tests), and treating those who are infected with H. pylori using antibiotics and proton pump inhibitors has been found to be effective in reducing stomach cancer incidence, with an estimated one-third reduction in risk. A programme based on this approach is likely to be cost-effective in New Zealand, and pro-equity particularly if targeted towards Māori and Pacific peoples. However, there are substantial gaps in our knowledge base that must be filled before such a programme can be considered.